(3QSGdI aj GdJUhas ((3YeQ Hf eMeO GdYjGT s)
(3ChdgG (B:s
,(3HYO GdMeO efG ddg ecJhH jTJed Ydi fhGRd RYeJe Cfg GdJHS Ydjce McegG s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3hgj YHGQI Yf eLehYI CSFdI SCdgG HYV GdfGS ddeDda aCLGH YfgGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs